UPAYA HUKUM TERHADAP PUTUSAN SELA SERTA PENGARUHNYA TERHADAP SUATU PERKARA PERDATA (STUDI KASUS DI PENGADILAN NEGERI DENPASAR) - Engelenburg Gunther, Wagner; Artadi, I Ketut; Ari Krisnawati, I Gusti Ayu Agung (Kertha Wicara : Journal Ilmu Hukum; Vol. 04, No. 01, Februari 2015, 2015)
The verdict serves as a tool or means of settling disputes. Therefore, it is expected that the verdict handed down should reflect the values of justice and truth by law so that it can be accepted especially by both parties of the litigants. In a case when there are parties who are not satisfied with the decision of the judge, or feel the verdict is not fair to them, so they are given the opportunity by the law, so that the decision can be corrected or reviewed by the judge of a higher level, namely through the legal remedy. The HIR and the RBg do not regulate in detail about the decision, as well as on its legal remedy in Law Number 20 of 1947. Against the interlocutory decision, the rejection over the competent exception, and incidental interlocutory decision regarding to intervention are open for legal remedies. While, the preparatory interlocutory decision, provisional, and interlocutory decision in specific forms, such as the local inspection command, the hearing of the expert testimony, there is no possible legal remedy. The type of research used in this legal writing is empirical method legal research.
Keywords: Exception of Competence, Intervention, Interlocutory Injunction/decision, Legal Remedies